Social Experience Guidance for College Students’ Entrepreneurship in the Social Network - Feng, Lili; Li, Ning; Huang, Tao; Bo, Huinan (International Journal of Emerging Technologies in Learning (iJET), 2022)
The low success rate of entrepreneurship is quite common for contemporary college students, and its main reason can be attributed to their lack of social experience and entrepreneurial guidance, thus, it’s of certain practical significance to study the social experience guidance for college students’ entrepreneurship and this paper aims to explore this problem based on social network. At first, this paper introduced the formation mechanism of the social experience guidance for college students’ entrepreneurship, proposed a novel Social Network Representation Learning (SNRL) method for college students’ entrepreneurship, which could attain more information of social experience guidance from networks with isomorphic substructures. Then, in the social network of college students’ entrepreneurship, this paper discussed the extraction method of structural subgraph of neighborhood space of college students and other entrepreneurial subject nodes, and proposed a method for building sub-networks similar to the scale and development state in the social network of college students’ entrepreneurship, and realized the information sharing of social and entrepreneurial experiences among sub-networks. At last, this paper constructed a Social and Entrepreneurial Experience Guidance (SEEG) model, and verified its effectiveness in experiments.